Studies on Pure Mlb® (Multiple Left Border) Technology and Its Impact on Vector Backbone Integration in Transgenic Cassava - Sahab, Sareena; Taylor, Nigel (Frontiers in Plant Science, 2022)
Imperfect T-DNA processing is common during Agrobacterium-mediated transformation, which integrates vector backbone sequences into the plant genome. However, regulatory restrictions prevent such transgenic plants from being developed for commercial deployment. The binary vector pCAMBIA2300 was modified by incorporating multiple left border (Mlb®) repeats and was tested in BY2 cells, tobacco, and cassava plants to address this issue. PCR analyses confirmed a twofold increase in the vector backbone free events in the presence of triple left borders in all three systems tested. Vector backbone read-through past the LB was reduced significantly; however, the inclusion of Mlbs® did not effectively address the beyond right border read-through. Also, Mlbs® increased the frequency of single-copy and vector backbone free events (clean events) twice compared to a single LB construct. Here, we briefly narrate the strength and limitations of using Mlb® technology and reporter genes in reducing the vector backbone transfer in transgenic events.